LEGO micro cities : build your own mini metropolis! - Friesen, Jeff (Photographer) (No Starch Press, Inc., 2019)
"Richly-illustrated guide to recreating classic architectural styles using only LEGO bricks, with suggestions for how to customize the buildings and create something completely new"--